Safety and efficacy of l‐valine produced by fermentation using Escherichia coli KCCM 80159 for all animal species. (28th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; Ramos, Fernando; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of l ‐valine (≥ 98.0%) produced by fermentation using a genetically modified strain of Escherichia coli (KCCM 80159). It is intended to be used in feed for all animal species and categories. Species identity of the production organism E. coli KCCM 80159 was confirmed; the strain was sensitive to antibiotics at concentrations below or equal to thresholds specified by EFSA; and no viable cells or its recombinant DNA were detected in the final product. Therefore, the final product does not give raise to any safety concern with regard to the genetic modification of the production strain. The FEEDAP Panel concludes that l ‐valine produced by E. coli KCCM 80159 is safe for the target species when supplemented in appropriate amounts to the diet according to the nutritional needs of the target species, for the consumer, for the users and for the environment. The product l ‐valine produced by fermentation using E. coli KCCM 80159 is regarded as an efficacious source of the essential amino acid l ‐valine for non‐ruminant nutrition. For the supplemental l ‐valine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen.